Analisis Kegiatan Ekstrakulikuler Kepramukaan untuk Membangun Karakter Disiplin Siswa di MI Al Hidayah 1 Kecamatan Cilodong Kota Depok - Saidatul Aliyah; Herlina; Siti Hadiyanti Dini I (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Scout activities are carried out in an organized manner by students outside of study hours. Scout activities have groups based on the age of the students. Scout activities have the aim of forming students' disciplined character. This research was conducted at Madrasah Ibtidaiyah Al – Hidayah I Cilodong Depok. The results of observations on extracurricular activities show that there are still students who are not good at discipline, it is proven that many of them are excused from scouting for family events and other reasons. This research aims to analyze